Legal Protection of Workers Against Overtime Work Practices Without Wage Payment Based on Law Number 6 of 2023 Concerning Job Creation - Fabiani Nur Ayesha El Adawiyah; Endang Sutrisno (Riviera Publishing, 2026)
Problems regarding the implementation of overtime work without the payment of overtime wages are still frequently found in employment relationships, even though the protection of these rights has been regulated under Law Number 6 of 2023 concerning Job Creation and Government Regulation Number 35 of 2021. This study aims to examine the forms of legal protection for workers who do not receive overtime wages and to analyze the law enforcement mechanisms applied to companies that disregard workers’ normative rights. This study uses a normative juridical method with a conceptual approach, strengthened by interview data from the Manpower Office, the Regional Technical Implementation Unit (Unit Pelaksana Teknis Daerah/UPTD) for Manpower Supervision Region III Cirebon, and workers. The results of the study show that the provision of overtime wages is a legal obligation that must be fulfilled by companies for workers who work beyond normal working hours. However, violations of this obligation still occur for various reasons, including limitations in companies’ financial conditions and companies’ operational demands. Legal protection for workers is carried out through preventive measures in the form of guidance, public dissemination, and labor supervision, as well as repressive measures through inspections, the issuance of inspection memorandums, and the application of criminal sanctions. These findings show that the effectiveness of legal protection for overtime wage rights still requires strengthened supervision and law enforcement so that workers’ normative rights can be optimally fulfilled.